Tax Holiday and Investment in Indonesia - Rukmi Juwita; Riani Tanjung; Edwin Karim (Faculty of Economics and Business, University of Pasundan, 2016)
Tax holiday is a facility given by the government to investors in Indonesia to attract foreign and local investors in Indonesia, especially in the industrial sector as well as to improve national economic growth. Purpose of this research is to analyze the tax holiday policy and how the impact on the investment in Indonesia. Data consists of primary and secondary data which are collected through interview, questionnaire and literature study. Respondents are Honam Petrochemical Corp, PT. Asahimas Chemical, PT. Nippon Shokubai, PT Petrokimia Butadiene Indonesia and PT. Ebel Industries. The results showed that all companies meet the criteria to obtain the facility of tax holiday. Giving tax holiday facility is very influential against the growth of industry in Indonesia especially for petrochemical industries that has an important role in the economic growth.